Reflections on Constructing Social Problems - Miller, Gale (SocietàMutamentoPolitica, 2018)
This paper is a reflection on Spector and Kitsuse’s claims-making approach to social problems construction, and to the subsequent studies that the approach inspired. Spector and Kitsuse argued that social problems are constructed as putative conditions that justify societal responses designed to manage, if not eliminate, them. Early sections of the paper examine basic themes in the constructionist literature on social problems. Two major themes in this literature focus on how social problems claims-making activities orient to social policy development and institutional interventions. Later sections consider two ways in which the constructionist approach might be expanded to consider additional claims-making contexts and constructionist perspectives. Social problems claims-making in popular culture contexts and Burke’s dramatistic perspective are discussed as examples of how constructionist studies of social problems might be expanded upon.